Learning Community at State Senior High School 1 Kuta Cot Glie Aceh Besar, Indonesia: An Analysis of Relationship Management - Nazaruddin; Cut Intan Salasiyah (Journal Informatic, Education and Management (JIEM), 2026)
This study investigates the important role of principal relationship management in creating and maintaining a good learning community in educational settings. The focus of the study is how principals can influence institutional performance, including improving the quality of learning, teacher satisfaction, and greater school community participation. A qualitative approach was used in this study. The case study was conducted in State Senior High School 1 Kuta Cot Glie Greater Aceh to see how the principal's interaction with various stakeholders in the learning community works. The results of the study indicate that a relationship approach based on trust, collaboration, and participatory is an important component in planning, organizing, implementing and evaluating strong and high-achieving learning community activities.